Decline in the Use of Medicalized Yoga Between 2002 and 2012 While the Overall Yoga Use Increased in the United States: A Conundrum - Avinash R. Patwardhan MD; Lynne (Way) (SAGE Publishing, 2017)
We analyzed the National Health Institute Survey Alternative Medicine supplement yoga data for 2002, 2007, and 2012 to answer the following questions: (1) Do the claims about increase in the use of yoga hold true at the level of specific health problems? (2) Do trends support a proposition that yoga is believed to be helpful in amelioration of disease conditions? (3) Do the prescribing patterns of health care providers correspond with the increasing popularity of yoga? Data were analyzed using SAS software, version 9.4. Response percentages were compared using chi-square test after adjusting for age. Between 2002 and 2012, use of yoga increased but adherence failed to increase, and use for specific health problems and for back pain declined; use of health care providers' referral-driven yoga declined between 2007 and 2012. All results were statistically significant. Our results suggest that the use of medicalized yoga declined between 2002 and 2012.